Pengaruh Video Edukasi terhadap Tingkat Pengetahuan tentang APAR pada Pekerja Stationery di PT X Tangerang - Purba, Fransiska Marsaulina Angelia Veronica; Widjanarti, Maria Paskanita; Haryati, Sri (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Production activities carried out by PT X Tangerang have high risk to cause a fire hazard, which in 2010 there was an incident of forklift. 90% of stationery workers did not have enough knowledge about fire extinguisher. This study aimed to analyze the effect of educational video towards the level of knowledge about fire extinguisher for stationery workers at PT X Tangerang. This research was an experimental study with quasi experimental method with nonequivalent control group design. Respondents were taken from stationery workers at PT X Tangerang with 21 workers in each experimental and control group. The sampling technique being used was purposive sampling and simple random sampling. The result of the analysis in the experimental group using the Marginal Homogeneity test showed that there was a significant effect (p = 0.000) in level of knowledge about fire extinguisher before and after received treatment with educational video, meanwhile no significant effect (p = 0.157) for those who was in the control group to their level of knowledge about fire extinguisher that was not given treatment. The result of the Chi Square test obtained a p value of 0.008 which means there was a significant effect from the educational videos towards the level of knowledge about fire extinguisher between the experimental group and the control group. The conclusion of this study is educational video has a significant effect towards the level of knowledge about fire extinguisher for stationery workers at PT X Tangerang.